Support modification to improve the sulphur tolerance of Ag/Al2O3 for SCR of NOx with propene under lean-burn conditions - Jagtap, Neelam; Shubhangi B. Umbarkar; Miquel, Pierre; Granger, Pascal; Dongare, Mohan K. (Applied Catalysis B-Environmental, 2009)
Ag/Al2O3 catalysts with 1 wt% SiO2 or TiO2 doping in alumina support have been prepared by wet impregnation method and tested for sulphur tolerance during the selective catalytic reduction (SCR) of NOx using propene under lean conditions, Ag/Al2O3 showed 44% NOx conversion at 623 K, which was drastically reduced to 21% when exposed to 20 ppm SO2. When Al2O3 support in Ag/Al2O3 Was doped with 1 wt% SiO2 or TiO2 the NOx conversion remained constant in presence of SO2 showing the improved sulphur tolerance of these catalysts. Subsequent water addition does not induce significant deactivation. On the contrary, a slight promotional effect on the activity of NO conversion to nitrogen is observed after Si and Ti incorporation. FTIR study showed the sulphation of silver and aluminum sites of Ag/Al2O3 catalysts resulting in the decrease in the formation of reactive intermediate species such as -NCO, which in turn decreases NOx conversion to N-2. In the case of Ag/Al2O3 doped with SiO2 or TiO2, formation of silver sulphate and aluminum sulphate was drastically reduced, which was evident in FTIR resulting in remarkable improvement in the sulphur tolerance of Ag/Al2O3 catalyst. These catalysts before and after the reaction have been characterized with various techniques (XRD, BET surface area, transmittance FTIR and pyridine adsorption) for physico-chemical properties. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag/Al2O3; Aluminum sulphate; DRIFTS; Selective catalytic reduction; Silver sulphate; SiO2; Sulphur tolerance; TiO2